2020
DOI: 10.1590/1807-1929/agriambi.v24n10p647-655
|View full text |Cite
|
Sign up to set email alerts
|

Soil physical quality in response to intensification of grain production systems

Abstract: The Brazilian Cerrado stands out in relation to grain production, however, in this region the occurrence of summer and irregular rainfall, drastically harm the non-irrigated production. Conservationist managements favor the soil physical quality and, consequently, the efficiency of soil water consumption. The objective of this study was to evaluate the soil physical quality, as a function of the conservation managements adopted, by using physical soil quality indicators, and to verify its relation with the soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Therefore, the duration of our study was not sufficient to provide strong evidence of differences in soil physical quality evaluated by porosity and static indicators, even though it showed strong differences when evaluating dynamic attributes, such as soil and water losses, as discussed above. In the same experimental area, Mota et al [6] observed that porosity-based indicators did not correlate with grain yield, but the pore size distribution indicator and organic carbon were effective in distinguishing the cropping systems. Silva et al [16], in the same experimental area, observed that soil and water losses were negatively correlated with crop yield and vegetation cover rate.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, the duration of our study was not sufficient to provide strong evidence of differences in soil physical quality evaluated by porosity and static indicators, even though it showed strong differences when evaluating dynamic attributes, such as soil and water losses, as discussed above. In the same experimental area, Mota et al [6] observed that porosity-based indicators did not correlate with grain yield, but the pore size distribution indicator and organic carbon were effective in distinguishing the cropping systems. Silva et al [16], in the same experimental area, observed that soil and water losses were negatively correlated with crop yield and vegetation cover rate.…”
Section: Discussionmentioning
confidence: 98%
“…Considering the study area formed by a large experimental block, a completely randomized design was adopted, as recommended by Ferreira et al [28] and successfully used in previous studies of long-term field experiments [29,30] and also in the same experiment in anterior studies [6,16,31]. Thus, for soil losses, water losses, penetration resistance, total porosity, macroporosity, microporosity, and soil bulk density, the different cropping systems (seven treatments) were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A utilização de plantas de cobertura como premissa para o sistema de semeadura direta atua como principal ferramenta, principalmente quando se trata de espécies forrageiras devido ao seu potencial de aumento na relação carbono/nitrogênio, através da lenta deposição de resíduos, que, indiretamente, protege o solo contra a perda de água e variação de temperatura (MOTA et al, 2020).…”
unclassified